Sodium Tanshinone IIA Silate Alleviates High Glucose Induced Barrier Impairment of Human Retinal Pigment Epithelium through the Reduction of NF-κB Activation via the AMPK/p300 Pathway. (1st February 2020) - Guo, Ze-Li; Li, Yu; Liu, Xiao-Wen; Wu, Miao-Yan; Guo, Qi; Yao, Xiang-Chao; Wang, Yan-Dong; Wu, Wen-Yu
ABSTRACT: Purpose: The disruption of retinal pigment epithelium (RPE) barrier may perform a crucial role in the pathogenesis of diabetic retinopathy (DR). AMPK exerts several salutary effects on photoreceptors and the RPE function and improves retina abnormalities. The current study aimed to determine whether sodium tanshinone IIA silate (STS) has an inhibitory effect on ARPE-19 cell monolayer permeability under high glucose conditions, and establish the underlying mechanism. Methods: We used a model of high glucose (25 mmol glucose, HG) condition mimicking diabetes in ARPE-19 cells, to assess the protective effects of STS. The barrier function of RPE cells were measured by Transepithelial Electrical Resistance (TEER) and fluorescein isothiocyanate (FITC)–dextran permeability. The interaction of NF-κB p65 and p300 were tested using immunoblotting and immunoprecipitation and immunofluorescence assay. Protein levels were assayed using Western blot. Results: We found STS promoted the phosphorylation of AMP-activated protein kinase (AMPK) at T172 in RPE cells, and STS treatment thus inhibited ARPE-19 cell monolayer permeability under HG condition, similar to the permeability under normal glucose (5.5 mmol glucose, NG). Moreover, we found that STS obviously prevented the colocalization of NF-κB and p300, and significantly inhibited their binding, subsequent decreased ARPE-19 cell monolayer permeability. Notably, Compound C (CC), a specific inhibitor of AMPK, blocked STS-mediated inhibition of ARPE-19 cell monolayer permeability. Conclusions: STS inhibited HG-induced RPE permeability possibly through the reduction of NF-κB activation via the AMPK/p300 pathway. The protective effects of STS were attained through the suppression of p300-mediated NF-κB acetylation and STS might be utilized for treatment of DR, in terms of preventing inflammation.